2006
DOI: 10.1111/j.1572-0241.2006.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Third-Line Rescue Therapy with Levofloxacin After Two H. pylori Treatment Failures

Abstract: Levofloxacin-based rescue therapy constitutes an encouraging empirical third-line strategy after multiple previous H. pylori eradication failures with key antibiotics such as amoxicillin, clarithromycin, metronidazole, and tetracycline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 23 publications
2
48
0
3
Order By: Relevance
“…On the other hand, empirical treatment after two failed attempts has shown heterogeneous results: 65-85% with bismuth-containing quadruple therapies [Hsu et al 2008;Gisbert et al 2014], 60-90% with levofloxacin-based therapy [Sereni et al 2012;Tursi et al 2012;Gisbert et al 2006;Zullo et al 2003a] and 62-95% with a rifabutinbased therapy associated with PPIs and amoxicillin [Lim et al 2014;González et al 2007]. The studies differ in terms of previously administered therapies, study populations and drug schedules.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, empirical treatment after two failed attempts has shown heterogeneous results: 65-85% with bismuth-containing quadruple therapies [Hsu et al 2008;Gisbert et al 2014], 60-90% with levofloxacin-based therapy [Sereni et al 2012;Tursi et al 2012;Gisbert et al 2006;Zullo et al 2003a] and 62-95% with a rifabutinbased therapy associated with PPIs and amoxicillin [Lim et al 2014;González et al 2007]. The studies differ in terms of previously administered therapies, study populations and drug schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Levofloxacin-based 'rescue' regimens It has been suggested that levofloxacin-based therapies may also represent an alternative when two (or more) consecutive eradication treatments have failed to eradicate the infection [Nishizawa et al 2009;Hsu et al 2008;Rokkas et al 2006;Gisbert et al 2006aGisbert et al , 2006bGisbert et al , 2005aCoelho et al 2005;Gatta et al 2005;Bilardi et al 2004;Zullo et al 2003aZullo et al , 2001a. As an example, a recent study by Zullo et al [2003a] aimed to evaluate the efficacy of a levofloxacin-amoxicillin-PPI combination in patients who previously had failed two or more therapeutic attempts, and eradication rate was 83% (intention-to-treat analysis).…”
Section: Amoxicillin±tetracycline-based Regimensmentioning
confidence: 99%
“…Therefore, the position in the case of therapy failure would be clear: do not readminister any of the antibiotics against which H. pylori has probably become resistant [Howden and Hunt, 1998;Lam and Talley, 1998]. (9) Finally, relatively high eradication rates have been obtained with empirical third-line treatment after two consecutive failures in several studies [Gisbert et al 2008b[Gisbert et al , 2006a[Gisbert et al , 2006b[Gisbert et al , 2004[Gisbert et al , 2003 However, limited experience suggests that endoscopy with culture and susceptibility testing may be appropriate after failure of two eradication therapies; in this situation, a nonrandomized retrospective study suggests that third-line therapy directed by the results of sensitivity testing improve eradication compared to further empirical antibiotics, demonstrating that the success rate of sensitivity-directed therapy is superior to PPI-amoxicillin-rifabutin triple therapy, and therefore suggesting that endoscopy and sensitivity testing at this point may be worthwhile rather than more widespread use of rifabutin-based regimens [Beales, 2001]. Cammarota et al…”
Section: Introductionmentioning
confidence: 99%
“…1 Similarly, some years ago we obtained encouraging results with a third-line combination of PPI-amoxicillinlevofloxacin in a Spanish pilot study. 5 We have just ) seem encouraging, especially when it is taken into account that our rescue regimen was prescribed empirically after two eradication failures. Furthermore, this regimen was well-tolerated, with adverse effects reported in 19% of the patients, and most were mild to moderate in severity and transient: myalgia (8%), nausea (6%), metallic taste (5%), abdominal pain (3%), and diarrhoea (3%).…”
mentioning
confidence: 84%
“…[5][6][7][8][9][10] Mean eradication rate calculated from these six studies was 73%. However, the sample size of the individual studies was low, with only 350 in total when all studies were considered.…”
mentioning
confidence: 97%